SAVEUS: SAving Victims in Earthquakes through Unified Systems. (1st January 2013) - Beard, Cory; Chen, Zhi Qiang; Kumar, Vijay; Lee, Yugyung; Leon-Salas, W. Daniel; Rao, Praveen
Natural disasters such as earthquakes damage the systems that are designed to confine the damage they cause. Many schemes have been suggested to minimise the damage but there is no single scheme that is equally effective in all types of natural disasters. Our hypothesis is that if relevant information about the event (during and after it ends) is gathered and disseminated in a timely manner, then we can significantly minimise the damage. We envision a system to deal with earthquakes in real-time that is called SAVEUS and has three main innovative components. The first component, called the rescue social network ( RSN ), gathers useful information from the general public and first responders and deposits it to the second component called agile knowledge base ( AKB ) that stores and processes information. The third component is called the rescue sensor network ( RSeN ) that discovers victims (survivors) and saves the information in the AKB .